2016
DOI: 10.1038/srep24066
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene positively regulates cold tolerance in grapevine by modulating the expression of ETHYLENE RESPONSE FACTOR 057

Abstract: Ethylene (ET) is a gaseous plant hormone that plays essential roles in biotic and abiotic stress responses in plants. However, the role of ET in cold tolerance varies in different species. This study revealed that low temperature promotes the release of ET in grapevine. The treatment of exogenous 1-aminocyclopropane-1-carboxylate increased the cold tolerance of grapevine. By contrast, the application of the ET biosynthesis inhibitor aminoethoxyvinylglycine reduced the cold tolerance of grapevine. This finding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
95
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 59 publications
6
95
0
Order By: Relevance
“…Ethylene plays important roles in regulating responses to a wide variety of external environmental stimuli, and ERFs are crucial components for relaying the ethylene signalling (Yang et al ., ). Several ERFs have been previously reported to be induced by ethylene, such as JERF1 (Zhang et al ., ), OsERF1 (Hu et al ., 2008b), and VaERF057 (Sun et al ., ), suggesting that these genes may be implicated in the ethylene signalling pathway to orchestrate stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Ethylene plays important roles in regulating responses to a wide variety of external environmental stimuli, and ERFs are crucial components for relaying the ethylene signalling (Yang et al ., ). Several ERFs have been previously reported to be induced by ethylene, such as JERF1 (Zhang et al ., ), OsERF1 (Hu et al ., 2008b), and VaERF057 (Sun et al ., ), suggesting that these genes may be implicated in the ethylene signalling pathway to orchestrate stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…However, stress-related genes at transcriptionallevel pattern have been identified by CK but the exact role of CK in cold stress is still unknown (Zwack & Rashotte 2015). Ethylene was proved to increase during low temperature in grapevine (Sun et al 2016). Finally, phytohormones engineering is very promising in plant response to environmental stresses; however, more research is still needed in this field (Wani et al 2016).…”
Section: The Effect Of Phytohormones On Plant Cold Tolerancementioning
confidence: 99%
“…Overall, these observed changes in TF transcript levels may be involved in controlling the fruits’ molecular adjustments to low storage temperatures. Furthermore, we found that LTC markedly affected the responses to two important phytohormones – ABA and ethylene – both known to be involved in stress responses and acquisition of cold‐stress tolerance (Chandler & Robertson, ; Hughes & Dunn, ; Thomashow, ; Sun et al ., ). In general, the LTC + chilling treatment activated the ABA signalling pathway by upregulating the ABA receptor PYL gene while downregulating two ABA catabolism genes and simultaneously repressed the ethylene signalling pathway by downregulating the ethylene biosynthesis gene ACO and upregulating the CTR1 gene that acts as a negative regulator of ethylene signalling (Fig.…”
Section: Discussionmentioning
confidence: 97%